The Inspection Panel : Annual Report, August 1, 2000 to July 31, 2001 - World Bank (Inspection Panel Annual Reports, 2001)
This Annual Report, which covers the period August 1, 1999 to July 31, 2000, has been prepared by the members of the Inspection Panel for the International Bank for Reconstruction and Development (IBRD) and the International Development Association (IDA) in accordance with the Resolution that established the Panel. The Report is circulated to the President and Executive Directors of both institutions. Subject ot Board approval, the three-member Panel is empowered to investigate problems that are alleged to have arisen as a result of the Bank not having complied with its own operating policies and procedures